Analysis of clinical nurse educators’ mentoring feedback on new nurse journals at a tertiary hospital in South Korea: utilizing text network analysis - Shinhye Ahn; Hye Won Jeong (BMC Nursing)
Abstract Background The gap between knowledge and clinical practice causes stress and reality shock, contributing to low job satisfaction and high turnover among new nurses; in 2023, the turnover rate in South Korea reached 52.4%. Korean preceptorship programs are often too brief to adequately support new nurses’ adaptation. Clinical nurse educators (CNEs) play a crucial role in addressing these issues by offering knowledge transfer, emotional support, and career guidance. Therefore, strategies to strengthen CNEs’ coaching and mentoring skills are essential to support new nurses’ stable clinical adaptation. This study analyzed how CNEs mentored new hospital nurses by responding to their post-entry journals. Methods This study employed a quantitative content analysis. We used NetMiner 4.5.1 to conduct a text network analysis of 1,742 mentoring journal responses written by four CNEs for 120 new nurses at C University Hospital in South Korea between June 2021 and May 2022. Results The keyword “attitude” had the highest frequency (726), emphasizing the clinical importance of fostering positive attitudes among new nurses. The keyword network had average centrality measures of degree (.15), closeness (.43), and betweenness (.05). Keywords with high centrality, such as “attitude,” “importance,” “performance,” and “difficulty, highlighted mentoring practices focused on enhancing clinical judgment, nursing performance, and managing workplace challenges. Eigenvector analysis identified three subtopic groups with optimal modularity (.295). Subthemes included: 1) helping new nurses to improve their professional competence, 2) encouraging new nurses struggling to adapt to the field, and 3) empathy for new nurses’ burdens and stress. Conclusions The findings revealed that the CNEs’ mentoring feedback focused on encouraging new nurses to maintain a positive attitude, inspiring their personal and professional growth, and offering empathy and encouragement to help them cope with burdens and stress. Based on these findings, targeted training modules for CNEs and mentoring guidelines should be developed to further support new nurses’ adaptation to clinical practice.